KEBERLANJUTAN POTENSI WISATA SEJARAH DAN BUDAYA KOTA BATUSANGKAR KABUPATEN TANAH DATAR SUMATERA BARAT - Najmi, Najmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Batusangkar as the capital of Tanah Datar Regency as well as one of the centers of Minangkabau History and known as the City of Culture has tourism potential that sells, especially historical and cultural potential. Many historical stories can be used as important information for Tanah Datar to be used as tourism potential. The obstacle is that the local government has not been able to utilize this information as a tourism potential. In addition, the icon of Tanah Datar that has been attached to the Basa Pagaruyung Palace already has an attraction in terms of its building but not enough historical information has been obtained in the palace. This is related to the attractiveness of a tourist icon so that visitors are curious and get the latest information about history. This is what has not been packaged optimally. This will be further investigated and solutions will be provided to stakeholders and communities supporting tourism. The specific purpose of this study is to provide solutions to the government and the community in developing the tourism industry and identify indicators that make the slow development of tourism in Tanah Datar and researchers will offer solutions in the form of policies and other supporting aspects of the tourism industry in Tanah Datar Regency. . This research uses qualitative methods with a historical approach, namely using various documents related to tourism policies in Tanah Datar Regency.Keywords: Sustainability, Tourism Potential, History and Culture, Batusangkar.